2010
DOI: 10.1002/rmv.644
|View full text |Cite|
|
Sign up to set email alerts
|

Newly identified human rhinoviruses: molecular methods heat up the cold viruses

Abstract: Human rhinovirus (HRV) infections cause at least 70% of virus-related wheezing exacerbations and cold and flu-like illnesses. They are associated with otitis media, sinusitis and pneumonia. Annually, the economic impact of HRV infections costs billions in healthcare and lost productivity. Since 1987, 100 officially recognised HRV serotypes reside in two genetically distinct species; HRV A and HRV B, within the genus Enterovirus, family Picornaviridae. Sequencing of their approximately 7kb genomes was finalised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 161 publications
(278 reference statements)
1
71
1
2
Order By: Relevance
“…For example, bacterial surface polysaccharides stabilize polioviruses and facilitate cell attachment by increasing binding to the viral receptor (33,34). In any case, experiments in our laboratory and elsewhere demonstrated that the RV-C interaction with native HeLa cells or other cell lines (e.g., A549) is not sufficient for efficient virus entry and replication (5,6,35).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, bacterial surface polysaccharides stabilize polioviruses and facilitate cell attachment by increasing binding to the viral receptor (33,34). In any case, experiments in our laboratory and elsewhere demonstrated that the RV-C interaction with native HeLa cells or other cell lines (e.g., A549) is not sufficient for efficient virus entry and replication (5,6,35).…”
Section: Discussionmentioning
confidence: 89%
“…Viruses belonging to the RV-C species were only discovered in 2006 (1,2), some 50 y after the initial identification of other RVs (3), because these viruses are not detectable by standard tissue-culture techniques (4)(5)(6)(7). RV-Cs are of special clinical interest because they can cause more severe illnesses requiring hospitalization in infants and children compared with the RV-A or RV-B, and are closely associated with acute exacerbations of asthma (8)(9)(10).…”
mentioning
confidence: 99%
“…Clinically and biologically, they share many attributes with the other designated HRV species, HRV-A and -B. Most studies of HRV-C disease associations, typically focused on children from asthmatic and/or hospital-based populations (Arden & Mackay, 2010), have demonstrated a similarly broad range of clinical outcomes to those observed in HRV-A and -B infections and, indeed, with other respiratory viruses. Some studies show no difference in clinical outcome between HRV species (Lau et al, 2007;Piotrowska et al, 2009), whereas others provide evidence for a more frequent role of HRV-C in lower respiratory tract disease, febrile wheeze in infants and toddlers, and asthma exacerbations in older children (Lau et al, 2007;Khetsuriani et al, 2008;Miller et al, 2009a;Wisdom et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically and biologically, they share many attributes with the other designated HRV species, HRV-A and -B. Most studies of HRV-C disease associations, typically focused on children from asthmatic and/or hospital-based populations (Arden & Mackay, 2010), have demonstrated a similarly broad range of clinical outcomes to those observed in HRV-A and -B infections and, indeed, with other respiratory viruses. Some A full list of all HRV-C variants characterized to date, categorized into a total of 61 confirmed or provisionally assigned types, is available with the online version of this paper.…”
mentioning
confidence: 99%
“…One disadvantage associated with the use of RV 5=-UTR primers is nonspecific amplification of human genomic DNA (chromosome 6) or RNA (large regulator noncoding RNA B2) sequences, yielding a nonspecific 424-bp product that is similar in size to the virus-specific amplicon (390 bp) (19)(20)(21). The nonspecific results are typically found in a small subset of nasal lavage fluid samples but are more common when clinical samples contain high concentrations of human RNA or contaminating genomic DNA (e.g., cases of intense cellular inflammation in airways or nasal brushing samples).…”
mentioning
confidence: 99%